Students' Learning Interest Using Computer and Android in Acid Base Teaching - Milanda Putri; Yenni Kurniawati (J-PEK (Jurnal Pembelajaran Kimia), 2021)
This research is motivated by the influence of high technology on education; hence educators need to choose the right technology device to use and compare student learning interests with and without the support of computer and android multimedia.  It was quasi-experiment research with posttest only and non-equivalent control group designs.  The subjects of this research were the eleventh-grade students of Natural Science. There were 2 sample classes—the eleventh-grade students of Natural Science 3 (experiment I) taught using computer multimedia, and the students of Natural Science 1 (experiment II) taught using android multimedia. Interview with teachers, preliminary data test that was homogeneity test, final data test, learning interest questionnaire, interview, observation, and documentation were used to collect the data. The analysis result showed that the learning interest percentage of experiment I was 73.88% with the high category, and experiment II was 81.19% with the very high category.  An independent t-test was used to see whether there was a significant difference between experiments I and II. It showed a significant difference in chemistry learning interest between students taught by using computer-based multimedia and those taught by using android-based multimedia on the acid-based lesson of chemistry subject at the eleventh grade of Natural Science.  Therefore, Android-based learning could be developed in the learning process to support student chemistry learning interests.REFERENCESAnugraheni, P. (2017). Pengaruh Pembelajaran 5E Learning Cycle Berbantuan Multimedia terhadap Minat Belajar IPA. Jurnal EDUSAINS, 9(1), 1–9.Fatma, A. D., & Partana, C. F. (2019). Pembelajaran Berbantu Aplikasi Android untuk Meningkatkan Kemampuan Pemecahan Masalah Kimia. Jurnal Inovasi Pendidikan IPA, 5(2), 229–236.Fauziah, A., Rosnaningsih, A., & Azhar, S. (2017). Hubungan Antara Motivasi Belajar Dengan Minat Belajar Siswa Kelas IV SDN Poris Gaga 05 Kota Tangerang. Jurnal JPSD, 4(1), 47–53. https://doi.org/10.21831/jpv.v5i3.6490Hamid, A., Santoso, R., & Widanarko, N. A. (2017). Tabel Periodik Kimia Berbasis Aplikasi Android. Indosian Journal on Networking and Security, 6(4), 27–31.Harefa, N., Tafonao, G. S., & Hidar, S. (2020). Analisis Minat Belajar Kimia Siswa Melalui Pembelajaran Berbasis Multimedia. Paedagoria: Jurnal Kajian, Penelitian Dan Pengembangan Kependidikan, 11(2), 81–86.Hemayanti, K. L., Muderawan, I. W., & Selamat, I. N. (2020). Analisis Minat Belajar Siswa Kelas XI MIA Pada Mata Pelajaran Kimia. Jurnal Pendidikan Kimia Indonesia, 4(1), 20–25. https://doi.org/10.23887/jpk.v4i1.24060Khairiyah, N., Indrawati, H., & Haryana, G. (2018). Effect of Learning Toward Learning Achievement on Economic Learning Eye Students Class XI IPS MAN 1 Pekanbaru. Jurnal Online Mahasiswa FKIP, 5, 1–15.Kurniawati, Y. (2017). Analisis Kesulitan Penguasaan Konsep Teoritis dan Praktikum Kimia Mahasiswa Calon Guru Kimia. Konfigurasi : Jurnal Pendidikan Kimia Dan Terapan, 1(2), 146–153. https://doi.org/10.24014/konfigurasi.v1i2.4537Kurniawati, Y., Wigati, M. R., & Hasri, S. (2021). Information And Communications Technology (ICT) Based Of Chemistry Instructional Learning Design For Students With Multiple Intelligence. Journal of Physics: Conference Series, 1–8. https://doi.org/10.1088/1742-6596/1779/1/012062Lina, F., & Artina, D. (2017). Studi Pendahuluan: Penerapan Praktikum Kimia Organik Berorientasi Aplikasi (Application-Oriented). Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 05(01), 41–46.Linda, R., Herdini, & Rahmaputri, Z. (2017). Multimedia Interaktif Berbasis Autoplay Media Studio 8 Untuk Mata Pelajaran Kimia Pokok Bahasan Laju Reaksi Untuk Kelas XI SMA/MA. Jurnal Pendidikan Kimia, 9(3), 341–346. https://doi.org/10.24114/jpkim.v9i3.8382Lubis, I. R., & Ikhsan, J. (2015). Pengembangan Media Pembelajaran Kimia Berbasis Android Untuk Meningkatkan Motivasi Belajar dan Prestasi Kognitif Peserta Didik SMA. Jurnal Inovasi Pendidikan IPA, 1(2), 191–201. https://doi.org/10.21831/jipi.v1i2.7504Lutfiani, W., Lukum, A., & Rumampe, O. (2016). Identifikasi Minat Belajar Kimia Pada Siswa Kelas X SMA Negeri Sekota Gorontalo. Jurnal Entropi.Pasaribu, D. S. (2017). Upaya Meningkatkan Minat dan Hasil Belajar Fisika Siswa Dengan Menggunakan Model Pembelajaran Talking Stick Pada Materi Listrik Dinamis di Kelas X SMAN 10 Muaro Jambi. Jurnal EduFisika, 2(1), 61–69. https://doi.org/https://doi.org/10.22437/edufisika.v2i01.4043Rajagukguk, W. (2011). Perbedaan Minat Belajar Siswa Dengan Media Komputer Program Cyberlink Power Director Dan Tanpa Media Komputer Pada Pokok Bahasan Kubus Dan Balok Di Kelas Viii Smp Negeri 1 Hamparan Perak Tahun Ajaran 2009/2010. Jurnal Pendidikan Matematika, 5(2), 205–220. https://doi.org/10.22342/jpm.5.2.599.Ratnasari, I. W. (2017). Hubungan minat belajar terhadap prestasi belajar Matematika. Jurnal Psikoborneo, 5(2), 400–405.Rochmani, N. L. I., Agustini, R., & Mitarlis. (2018). Development Of Student Worksheet Based On Guided Inquiry Model On Electrolyte And Non Electrolyte Solution Matter To Train The Science Process Skills In X Grade Senior High School. Jurnal Pendidikan Kimia UNESA, 7(1), 46–51. https://doi.org/10.29210/20181100Rozikin, S., Amir, H., & Rohiat, S. (2018). Hubungan Minat Belajar Siswa dengan Prestasi Belajar Siswa pada Mata Pelajaran Kimia di SMA Negeri 1 Tebat Karai dan SMA Negeri 1 Kabupaten Kepahiang. Jurnal Pendidikan Dan Ilmu Kimia, 2(1), 78–81.Suryani, A. E., Basir, M. D., & Rusmin, A. (2014). Pengembangan Multimedia Pembelajaran Berbasis Komputer Model Permainan Pada Mata Pelajaran Ekonomi di SMA Muhammadiyah 1 Palembang. Jurnal Profit, 1(1), 1–13.Syardiansah. (2016). Hubungan Motivasi Belajar dan Minat Belajar terhadap Prestasi Belajar Mahasiswa Mata Kuliah Pengantar Manajemen ( Studi kasus Mahasiswa Tingkat I EKM A Semester II ). Jurnal Manajemen Dan Keuangan, 5(1), 440–448.